Cell polarity in development and disease - Tepass, Ulrich (Current topics in developmental biology ;, 2023)
Cell Polarity in Development and Disease, Volume 154 in the Methods in Cell Biology series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of timely topics, including Cell polarity in the protist-to-animal transition, Polarized actin networks in development: Case studies from Drosophila, Protein clustering and cell polarization, Polarity in the Drosophila female germline, Context Matters: Mechanisms governing epithelial polarization in C. elegans, Epithelial polarity in the fly: Principles and diversity, Polarizing epithelial expulsion and expulsion driven by mispolarization, The Role of Apical-Basal Polarization in the Mammalian First Cell Fate Decision, and much more.